E-Library Peminjaman dan Pengembalian Buku Berbasis Web dengan Metode Prototipe - Fika Dwi Yuli Astutik; Alvia Kharismasari; To Bagus Setyo Adi Laksono; Iman Santoso; Ahmad Chusyairi (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
The Library is a facility that is used as a place to access information. The library contains various information needed by the public with various books from various fields. In this digital era, not a few libraries still use conventional methods for data management processes. As records for borrowing and returning books that are still done manually, such as handwriting on large books. So it is not uncommon missing data. With this, the researcher aims to create a library information system that aims to make it easier for library staff to record loans and return books. The development method used is the prototype method. The conclusion obtained in this study is the e-library application can help users in the process of data collection and data management of borrowing and returning books.